2017
DOI: 10.1016/j.immuni.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen F Presents Peptides and Regulates Immunity through Interactions with NK Cell Receptors

Abstract: Summary Evidence is mounting that the major histocompatibility complex (MHC) molecule HLA-F regulates the immune system in pregnancy, infection, and autoimmunity by signaling through NK-cell receptors (NKRs). We present structural, biochemical and evolutionary analyses demonstrating that HLA-F presents peptides of unconventional length dictated by a newly arisen mutation (R62W) that has produced an open-ended groove accommodating particularly long peptides. Compared to empty HLA-F open conformers (OC), HLA-F t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 62 publications
(75 reference statements)
3
137
0
Order By: Relevance
“…While the precise functions of HLA-F are unclear, our observations that its expression level in the endometrium during the window of implantation is associated with fecundability 6 , and that it is up-regulated by progesterone implicates it in the establishment of pregnancy. Intriguingly HLA-F binds LIR and KIR natural killer cell receptors [13][14][15][16][17] , suggesting HLA-F expressed by DSCs directly signal to uterine natural killer (uNK) cells which are essential for the establishment of maternal immunotolerance and spiral artery remodeling. Consistent with this hypothesis HLA-F expression level is positively correlated with uNK abundance in mid-luteal endometria and is predictive of achieving pregnancy 6,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the precise functions of HLA-F are unclear, our observations that its expression level in the endometrium during the window of implantation is associated with fecundability 6 , and that it is up-regulated by progesterone implicates it in the establishment of pregnancy. Intriguingly HLA-F binds LIR and KIR natural killer cell receptors [13][14][15][16][17] , suggesting HLA-F expressed by DSCs directly signal to uterine natural killer (uNK) cells which are essential for the establishment of maternal immunotolerance and spiral artery remodeling. Consistent with this hypothesis HLA-F expression level is positively correlated with uNK abundance in mid-luteal endometria and is predictive of achieving pregnancy 6,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore HLA-F expression increases during gestation, reaching a peak at term 9,12 . Like other MHC-I molecules, HLA-F binds natural killer (NK) cell receptors from the LIR and KIR families, including LIR1 and LIR2 13,14 , KIR2DS4 and KIR3DL2 15 , and KIR3DL1 and KIR3DS1 14,16,17 . Uterine natural killer (uNK) cells, which are essential for the establishment and maintenance of maternal immunotolerance and spiral artery remodeling, express KIR3DL1 and LIR2 suggesting HLA-F expressed by EVTs and DSCs mediate interactions with uNK during implantation, trophoblast invasion, and establishment of the uteroplacental circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between inhibitory KIR and HLA class I proteins is well characterised, but the ligands of activating KIR genes remain largely elusive. KIR3DS1 has been shown to exhibit affinity for HLA Bw4 and HLA‐F (a non‐classical HLA class I molecule), and KIR2DS1 binds the C2 epitope . Evidence has indicated that KIR3DS1 binds to the HLA‐B*57:01 protein/peptide complex in a peptide‐dependent manner (an HLA allotype which contains the HLA‐Bw4 epitope), suggesting that in some cases the presentation of the cognate peptide within the HLA molecule's peptide binding groove is necessary to form a discontinuous epitope for KIR recognition .…”
Section: Kir Protein Activitymentioning
confidence: 99%
“…NT5E, which was upregulated in all MAPK mutants, promotes immunosuppression through the production of adenosine from AMP, which can decrease the capacity of natural killer cells to produce immune activating IFN molecules and prevents the clonal expansion of cytotoxic T cells in the surrounding tumor tissue (Gao et al, 2014). Conversely, HLA-F and DSE (also known as dermatan sulfate epimerase), were downregulated in all oncogene expressing cell lines, and both play a role in immune system activation and tumor-rejection, through activation of NK cells or cytotoxic T cells, respectively, in the tumor microenvironment (Dulberger et al, 2017;Liao et al, 2019). Both NT5E and HLA-F show reversed expression levels upon…”
Section: Alteration In Adhesion Moleculesmentioning
confidence: 99%
“…However, we do not know how expression of different oncogenes globally alters glycosylation on individual proteins at a proteome-wide scale. Very recently, hybrid type ETD methods, such as activated ion electron transfer dissociation (AI-ETD) and ETD with supplemental activation (EThcD), have emerged as forerunners for glycoproteomic profiling due to their ability to generate sequence informative tandem mass spectra that links both the peptide backbone and corresponding glycan modification (Liu et al, 2017;Riley et al, 2019;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%